THE DEVELOPMENT OF SCIENCE E-MODULE BASED ON PROBLEM-BASED LEARNING IN SIMPLE ELECTRICAL CIRCUIT MATERIAL - HC, Nurhikmah.; Siregar, Tiurlina; Samosir, Hotlan (Jurnal Ilmu Pendidikan Indonesia, 2023)
: This research conducted by applied Research and Development (Rnd). This research aims to make science e-module, science e-module development, science e-module validity, improvement of students’ activeness and learning result by using science e-module based on problem-based learning in simple electrical circuit material. This research was carried out at SDIT Qurrota A’yun Abepura with total of 29 sixth grade students as the sampling. The result of this research show that 1) There are 8 steps in making e-module 2) Development of science e-module based on problem-based learning in simple electrical circuit material is adapted with e-module development steps. 3) the feasibility of science module based on problem-based learning in simple electrical circuit material which consists of material validation, media validation, SDIT Qurrota A’yun teacher's responses, and student’s responses are good with the average feasibility score in 94,46% and categorized as very proper to use as teaching materials, 4) students’ activeness score in the first meeting with average score 71,66 and categorized as quite active, second meeting with average score 74,71 and categorized as quite active, and the third meeting with average score 82,26 and categorized as active 5) The improvement of learning result obtained an average of n-gain of 0,64 with a medium category, so it has a good impact in students’ mastery of simple electrical circuit.